INFLUENCING FACTORS OF E-GOVERNMENT SERVICES ADOPTION IN BOSNIA AND HERZEGOVINA - Edin Osmanbegović; Zijad Lugavić (Economic Review)
Worldwide, e-government is becoming very important in providing public services. Successful implementation of e-government depends on two sides. One side represents government with their view of e-government implementation, and at another side are citizens’, NGO’s and private sector as users of e-government services with their needs and views of e-government services. So, to make the successful implementation of e-government services, the government needs to take into account wishes (needs for digital services) of their citizens’. In that way, the government will prevent low-level of adoption and usage of e-government services, which is connected especially with developing countries. To address this issue, this study will try to identify key determinants affecting citizens’ adoption and usage of e-government services in Bosnia and Herzegovina. For that purpose, study adopted UTAUT model to identify and explore determinants of citizens’ adoption of e-government services. Regarding all previously mentioned, the main goal of this study can be defined as the way to identify key determinants affecting e-government adoption by citizens’ in the state of Bosnia and Herzegovina. The survey results, conducted on a sample of 553 citizens’ of Bosnia and Herzegovina, found that determinants social influence, effort expectancy and performance expectancy are statistically most influential determinants of citizens’ adoption of e-government services. Also, citizens’ adoption and usage of e-government services depend on citizens’ age, level of education and internet experience. The conclusion can be that successful e-government services implementation greatly depend on citizens’ adoption and usage of e-government services.